Safety Profile and Patient Satisfaction of the Routine use of Propofol in Gastrointestinal Endoscopy - Gurung, RB; Purbe, B; Malla, B; Dhungel, A; Yogol, S; Poudel, A; Konwor, K; Byanju, S (Kathmandu University Medical Journal, 2015)
Background Routine use of sedation in upper gastrointestinal endoscopy is uncommon in Nepal. There is no study on use of propofol sedation in routine endoscopy examination in Nepal. This study was conducted in order to assess the patient satisfaction and safety profile in patient undergoing routine upper GI endoscopic examination on outpatients.Objective To study safety profile and patient satisfaction of use of propofol in patients undergoing upper GI endoscopy.Method A prospective, observational study was conducted in the endoscopy unit of Dhulikhel hospital, Kathmandu University Hospital from July 2011 to 2012 July. Patients who were referred to upper GI endoscopy were offered to sedation under propofol. Informed consent was taken after explaining side effects, advantages and risk-benefit to the clients. The propofol was administered by the endoscopy nurse under guidance and supervision of the endoscopy performing physician.Data were collected and analyzed using SPSS version 16.0 with 0.05 level of significance.Result Total of 203 patients included in the study. Among 203 patients, 21. 2% were males and 78.8% were females; 83.7% were of less than of 60 years age and 16.3% above 60 years of age. The mean total dose of propofol required was 136.08 ± 48.82 mg. Total of 29.1 % of cases required O2 administration during the procedure time due to transient drop in O2 saturation. Total of 4.4% of cases required fluid administration due to transient fall in blood pressure. Total of 68.0% of cases were completely sedated; 28.6% had minor restless and 3.4% showed agitation during induction period of propofol sedation. Total of 99.5% of patients reported pleasant experience while 0.5% reported unpleasant. Among 203 respondents, 98.5% responded they would prefer to do the procedure under propofol sedation in the future; 1.5% responded they did not want sedations in the future.Conclusion Upper GI endoscopy can safely be performed under propofol sedation administered by registered trained nurse under the supervision of endoscopist.Kathmandu University Medical Journal Vol.12(2) 2014: 101-105